Pemakaian Gaya Bahasa Metafora dalam Cerita Fabel “Al- Diku Al-Zarifu” Karya Kamil Kailani - Ridwan, Rosya Afifa; Nurhuda, Zam-Zam; Hifni, Ahmad; Suparno, Darsita; Nisa’, Mauidlotun (Universitas Muhammadiyah Gorontalo, 2023)
This study aims to analyze the use of metaphorical language in the fable Al-Dīku Al-Żarīfu by Kamil Kailani. The method used in this research is descriptive analytic method with a qualitative approach. Data obtained through literature study and recording techniques. Data analysis was carried out using the equivalent technique between metaphors and their meanings as well as analytic descriptive techniques. The results of the study show that in the fable story Al-Dīku Al-Żarīfu by Kamil Kailani uses various kinds of metaphorical language styles which are quite diverse and creative in enriching the story. The use of metaphorical language style can be found in every part of the story, from character introduction to problem solving. Some of the metaphors found include personification, simile, metonymy and synesthesia. The use of metaphorical language style in the fable story Al-Dīku Al-Żarīfu can have a significant influence on the reader's understanding of the story. The use of metaphors makes it easier for the reader to imagine the situation that is happening and makes the story more lively and interesting. In addition, the use of metaphors also gives nuances of beauty and a deep impression to the story.